Fostering Tsunami Preparedness in Early Childhood: A Gamified Learning Approach for Banda Aceh - Fauzatul Uzma; Dewi Fitriani; Umar bin Abd Aziz (Journal of Islamic Education Students (JIES), 2026)
This study aimed to develop and assess the feasibility of a gamified digital learning media for tsunami disaster mitigation designed for early childhood education in Banda Aceh, a disaster-prone region. Using the Research and Development (R&D) method with the ADDIE model, the study involved 25 children from class A1 at TK IT Baitussalihin selected through total sampling. Data were collected through expert validation sheets and observation during field trials. The media, developed on the Educaplay platform as an interactive picture quiz titled “Fun Picture Quiz: Froggy Jumps,” obtained a final validation score of 100% from media and material experts, with an average expert score of 85% (Very Feasible). Field testing showed an overall feasibility score of 88% (Very Feasible), with 13 children achieving perfect scores and 12 scoring 75%. The findings indicate that the gamified media is engaging, visually appropriate, and pedagogically suitable for supporting early childhood cognitive development while addressing the need for interactive digital resources in tsunami preparedness. Further studies are recommended to examine its long-term effectiveness in enhancing children’s disaster preparedness knowledge.